Probabilistic loasd flow in HVAC/HVDC systems with high participation of intermitent renewable energy sources (2020)
The implementation of HVDC grids as an alternative for integrating renewable energy sources to AC power systems, adds important challenges in planning expansion and reliability assessment, taking into account that there must be tools that allow working with the uncertainty of renewable energies and the particularities of HVDC grids. This thesis presents the development of a probabilistic power flow (PPF) for HVAC-HVDC systems, which allows the inclusion of the effect of uncertainties of renewable energy sources. Two PPF methodologies are presented, Monte Carlo Simulation and 2m+1 Point Estimate Method, whose main strength lies in the fact that the modeling of renewable generation sources is based on general sampling data, therefore no further statistical information is required previously, which makes the difference with respect to other works presented. The methods are tested in a system with high participation of renewable sources, the modified XJTU-ROTS 2017 system.